2011
DOI: 10.1371/journal.pone.0027083
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix from Porcine Small Intestinal Submucosa (SIS) as Immune Adjuvants

Abstract: Porcine small intestinal submucosa (SIS) of Cook Biotech is licensed and widely used for tissue remodeling in humans. SIS was shown to be highly effective as an adjuvant in model studies with prostate and ovarian cancer vaccines. However, SIS adjuvanticity relative to alum, another important human-licensed adjuvant, has not yet been delineated in terms of activation of innate immunity via inflammasomes and boosting of antibody responses to soluble proteins and hapten-protein conjugates. We used ovalbumin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…It has shown promise as a cancer vaccine adjuvant against human prostate cancer by evoking effective cell-mediated immunity [17]. In an earlier study, we have reported the efficiency of SIS in augmenting the immunogenic potential of soluble protein antigens like ovalbumin and keyhole-limpet hemocyanin [18]. We also described that SIS exhibits adjuvanticity without inducing any adverse pathologic inflammatory response even in autoimmune prone NZB/WF1 mice [19].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has shown promise as a cancer vaccine adjuvant against human prostate cancer by evoking effective cell-mediated immunity [17]. In an earlier study, we have reported the efficiency of SIS in augmenting the immunogenic potential of soluble protein antigens like ovalbumin and keyhole-limpet hemocyanin [18]. We also described that SIS exhibits adjuvanticity without inducing any adverse pathologic inflammatory response even in autoimmune prone NZB/WF1 mice [19].…”
Section: Introductionmentioning
confidence: 94%
“…In this respect, SIS is better than some commercial adjuvants that often induce inflammatory tissue damage at sites of injection. The particulate nature of SIS may also promote phagocytosis, antigen uptake and retention by antigen presenting cells (APCs) [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when SIS was formulated into particles and combined with non-self antigens or hapten-protein conjugates, it increased the magnitude of the antibody response (primarily IgG1) against the antigens or haptens, again without promoting significant inflammation. 78 Little is known about which proteins are immunodominant, what the affinity of the antibody responses are, or how diverse of an antibody and T cell repertoire is generated, as titers have been measured against multi-component extracts of the implanted material. Conclusively identifying the epitopes and/or the main immunomodulating components that positively and negatively influence these processes is challenging.…”
Section: Immunological Outcomes Achievable With Biomaterialsmentioning
confidence: 99%
“…Serum antibody levels were measured and isotyping of antibodies performed by ELISA as described previously [26]. For all experiments plates were coated with 50 l of 10 g/ml sonicated S. aureus.…”
Section: Elisamentioning
confidence: 99%